Наезд по понятиям: Роман / Владимир Григорьевич Колычев - Колычев Владимир Григорьевич (Эксмо, 2004)
Экземпляры: ф.1 (20171120) / Инвентарный номер: 42650 / Цена: / Авт.знак: К61 / ББК: 84 (2Рос=Рус)6-44